Kendali Kecepatan Motor DC Menggunakan Chopper DC Dua Kuadran Berbasis Kontroller PI - Febri Rahmadi; Muldi Yuhendri (Jurnal Teknik Elektro Indonesia, 2020)
DC (Direct Current) motor is one of drive which is widely used in industry. DC motor as a drive has several advantages compared with AC (Alternating Current) motor. One of the advantages use DC motor as drive in industry because has a starting big torque and rotation speed motor can be set up easily in the range wide variation of rotation. One of speed setting DC motor can use DC Chopper two quadrant. Speed control DC motor with DC Chopper two quadrant is a method for speed control motor DC can operate for two condition which can be stated in the quadrant system. For one quadrant DC motor can operate for forward motoring and the second quadrant DC motor can operate for renegerative breaking. DC Chopper is a electronic circuits can change value voltage and current DC source, and can using for speed control and operate DC motor. For system control used controller PI (proportional integral) for feedback parameter mechanics and electrick DC motor. For controller PI can work for system control used Simulink software for programming, and also works for interfece to displays real times condition parameters work operate DC motor.